The 2014 European elections in Britain : the counter-revolt of the masses? - Parau, C (Faculty of Political Science, University of Bucharest, 2014)
This article reviews the campaign manifestoes of the main political parties vying in the UK's 2014 European Parliamentary elections, and analyses the electoral results. The most newsworthy event has been the meteoric rise of the United Kingdom Independence Party (UKIP), a vehemently Eurosceptic party advocating withdrawal from the EU. UKIP beat both mainline parties (Labour and the Conservatives) even while the vote collapsed for the UK's most Europhile party, the Liberal Democrats. Even more important is the influence UKIP has now won to affect the domestic electoral strategies of the Conservative and Labour Parties, with which it competes for the Eurosceptic centre-right and anti-immigration working-class vote, respectively. The Conservatives, in Coalition with the Liberal Democrats since 2010, were forced to reshuffle their Cabinet to give Eurosceptic MPs a higher profile; to pass a European Union Act mandating an in-out referendum on EU membership in 2017; and to persuade the EU to appoint a British Conservative to head the European Commission’s Financial Services Directorate. UKIP’s success has been stirring both fears and hopes for the (domestic) general election of 2015. An anti-statist party that combines elements of libertarianism and nationalism, UKIP may well come to embody the revolt of the masses against the British establishment.